The stepsister 2 - Stine, R. L. (New York : Simon Pulse, 2005)
The doctor says Nancy is cured--she's over the murderous rage that made her try to kill her sister Emily last year, and now she's home for good.
Keywords: Stepsisters -- Fiction; Anger -- Fiction; Horror stories